2022
DOI: 10.3389/fpls.2022.938284
|View full text |Cite
|
Sign up to set email alerts
|

Induced polyploidy deeply influences reproductive life cycles, related phytochemical features, and phytohormonal activities in blackberry species

Abstract: In some cases, polyploidy is an important phenomenon in the evolution of fruit crops. Polyploidy can be used in fruit breeding programs to develop varieties with higher yields and better fruit quality, as well as better adaptation to adverse environmental conditions. In this study, three wild species of blackberry were subjected to different degrees of induced polyploidy, and the effects of which were evaluated on morphological, physiological, and phytohormonal traits. With the aim of gaining a deep insight in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Similar results where induced polyploid genotypes demonstrated higher fruit weight and elevated sugar contents of the fruits have been previously reported [32][33][34]. These enhancements could be attributed to the changes in gene expression, involving both the upregulation and downregulation of processes related to biosynthesis, transport, reception of primary and secondary metabolites, and various enzymes [34,35]. Overall, these findings highlight the potential of synthetic polyploidization in improving desired fruit traits.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results where induced polyploid genotypes demonstrated higher fruit weight and elevated sugar contents of the fruits have been previously reported [32][33][34]. These enhancements could be attributed to the changes in gene expression, involving both the upregulation and downregulation of processes related to biosynthesis, transport, reception of primary and secondary metabolites, and various enzymes [34,35]. Overall, these findings highlight the potential of synthetic polyploidization in improving desired fruit traits.…”
Section: Discussionsupporting
confidence: 87%
“…This is a significant finding, as increased sugar content can enhance the sweetness and palatability of the fruits, potentially making them more appealing to consumers. Similar results where induced polyploid genotypes demonstrated higher fruit weight and elevated sugar contents of the fruits have been previously reported [32][33][34]. These enhancements could be attributed to the changes in gene expression, involving both the upregulation and downregulation of processes related to biosynthesis, transport, reception of primary and secondary metabolites, and various enzymes [34,35].…”
Section: Discussionsupporting
confidence: 87%
“…In tetraploid rice, the protein and amino acid levels rise, but the amylose concentration frequently declines ( Wang et al., 2022c ). Functional proteins, oils, vitamins, flavonoids, trace minerals, necessary amino acids, and functional and essential proteins are unique nutritional components found in rice ( Nam et al., 2018 ; Yang et al., 2019 ; Sabooni and Gharaghani, 2022 ; Zhang et al., 2022 ). Strong antioxidant properties of flavonoids were demonstrated by their ability to directly scavenge free radicals, inhibit the production of free radicals by the enzyme oxidase, chelate metal ions produced by free radicals, and promote the regeneration of antioxidant enzymes and small-molecular antioxidant factors ( Bors and Michel, 2002 ; Borges-Bubols et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following that, a number of academic and practical studies on high-fertility tetraploid rice were conducted, which encouraged the use of polyploid rice ( Ghaleb et al., 2020 ; Yu et al., 2020 ; Chen et al., 2021 ; Ku et al., 2022 ). In addition to causing gigantism, which increases biomass output, polyploidization also alters the nutritional quality of the organism; for instance, the levels of carbohydrates, proteins, vitamins, and alkaloids typically increase ( Sabooni and Gharaghani, 2022 ). However, rice loses some of its nutritious value as a result of polyploidization.…”
Section: Introductionmentioning
confidence: 99%
“…Sabooni et al [47] demonstrated that ploidy level correlated significantly with the total soluble solids in the leaves and with the number of pistils, leaf green index, and glucose content in floral nectar in blackberries (R. persicus, R. caesius, and R. sanctus). However, the content of polyphenols was not correlated with ploidy level but did depend on the bramble species and ploidy level.…”
Section: Ploidy Level and Biological Propertiesmentioning
confidence: 99%